Understanding Florida Residents’ Perceptions of and Experiences with Landscape Irrigation Restrictions: Insights for Water Conservation Experts as Well as Extension Educators - Sravani Pasula; Dharmendra Kalauni; Laura Warner; John Diaz; Ange Asanzi; James Harmon; Deirdre Irwin; Robin L. Grantham (EDIS)
This publication discusses Florida residents’ awareness and perceptions of irrigation restrictions to illuminate the processes that support or prevent their compliance with these policies. Written by Sravani Pasula, Dharmendra Kalauni, Laura Warner, John Diaz, Ange Asanzi, James Harmon, Deirdre Irwin, and Robin L. Grantham, and published by the UF/IFAS Department of Agricultural Education and Communication, May 2024.